Study Of Islamic Civilization In The Jahiliyah Period (Before 570 M) In The Field Of Politics - Nabilla Nurbaiti Zulaini; Zulfi Mubarok; Nurkholid (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2024)
The study of Islamic civilization during the jahiliyah period (Before 570 M) The field of politics is very important to be studied more deeply. This is because the study never ceases to be debated. The purpose of this paper is to understand 3 things: First, the political paradigm of the jahiliyah period (Before 570 AD) in the Political Field. Second, internal and external factors that influenced the politics of the jahiliyah (Before 570 M) period in the political field. Third, the positive and negative political implications of the jahiliyah (Before 570 M) period of politics on Muslims at that time. The method used qualitative research with a literature review approach is based on the theory of Mustika Zed, as for data collection by means of library research techniques and analyzed by collecting, reducing, displaying, and drawing conclusions. The results found 3 things: First, the political paradigm of the Jahiliyah period had 3 forms: (1) Discrimination (2) Social (3) Economic. Second, internally there are 3 factors that influence the politics of the Jahiliyah era: (1) power (2) customary law (3) protection. As for externally influencing the politics of the Jahiliyah period, there are 3 factors: (1) tribes, (2) geography, (3) tribes. Third, the positive implications for the politics of the Jahiliyah period are 3 halls: (1) Diversity of political systems (2) Moral improvement (3) Preserving cultural culture. Meanwhile, the negative implications for the politics of the Jahiliyah era are 3 things: (1) discrimination and oppression, namely unfair treatment and differences in the rights that exist in the community, (2) conflicts between groups, namely wars or clashes that occur between tribes, (3) The absence of morals, such as burial and murder of newborn girls. The conclusion that this paper shows that it shows that it provides a new view and insight into the study of Islamic civilization during the Jahiliyah period.